Bhīṣma, Droṇa y Karṇa: naturaleza y destino en la épica del Mahābhārata - Cattedra, Olivia María Margarita (2022)
This article will analyze, within the narrative framework of the Hindu epic, the outcome of three characters affected by conflicts between their nature and destiny. The clarification of these vital crossroads will be fundamental for the restoration of the cosmic balance and the dynamics of the One in the multiple..